Finite element modelling of compartment fire using ABAQUS - Ab. Kadir, Mariyana Aida (Penerbit UTM Press, 2015)
This paper presents finite element modelling (FEM) of a reinforced concrete (RC) frame subjected to elevated temperature. The work presented is part of the UK-India Education and Research Initiative (UKIERI) project. In this project, an experimental test of sub-assemblage frame with elevated temperature has been performed at Indian Institute of Technology (IIT) Roorkee, India. The finite element model using ABAQUS software has been used to validate the increased in temperature distribution on reinforced concrete frame exposed to fire. The idea of this study is to design a compartment fire, and determination of emissivity value at different height. And composition of hot gases was calculated. Gas temperatures used was based on the average temperature-curve obtained in the fire test. The validity of the finite element model was established by comparing the predicted values from the FEM with test data direct from fire test results. The results obtained indicate that suggested FEM analysis procedure is capable of modelling temperature in compartment fires